Scratching Responses to Epidermal Injury in C57BL/6, DBA/2, BALB/c, and CD1 Mice - Sargent, Jennifer L (Comp Med, 2016)
Whereas early investigations into ulcerative dermatitis (UD) focused on the possibility of a primary dermatopathology, several recent studies have advocated scratching behavior as a primary driver for UD. The aim of this study was to assess whether B6 mice exhibit excessive scratching under resting conditions or when provoked by epidermal barrier disruption. We hypothesized that B6 mice would exhibit more spontaneous scratching behavior and that B6 mice would be more pruritic after mild epidermal barrier injury compared with the other strains and stock tested. The behavior of the retired breeder female C57BL/6J, DBA/2J, BALB/cByJ, and Crl:CD1 mice was videotaped for 60 min. Behavior filming occurred at 17:15 and at 07:00 the next morning prior to (baseline) and after tape-stripping to initiate epidermal barrier disruption. Scratching duration was recorded as brief (less than 3 s) or prolonged (3 s or longer), on the basis of observations during a pilot study. In contrast to the hypothesis, B6 mice did not scratch significantly more frequently, have more long-duration scratching events, nor have a higher median scratching duration of prolonged scratching as compared with the other types of mice tested. In fact, B6 mice showed the lowest average scratching frequency and duration under both conditions. B6 mice demonstrated increased scratching behavior after epidermal barrier disruption, but the increased scratching did not surpass the rate or duration of scratching in the other types of mice tested. These findings do not support the idea that a strain-related tendency toward exaggerated scratching behavior under resting or epidermal barrier disruption conditions predisposes B6 mice to UD.